Integrasi Unsur Spiritualitas Dalam Prinsip Good Cooperative Governance: Revitalisasi Nilai Koperasi - Fitri Nur Rilah; Nur Indah Riwajanti (Jurnal Akuntansi dan Keuangan Islam, 2017)
The aim of this research was to examine the integration of spirituality element in Good Cooperative Governance (GCG) priciples. This was a qualitative post-modernist research. The research was conducted in one of small towns in East Java often called ‘Kota Santri/Islamic Student City’, namely Pasuruan City. The informants in this research were Head of Empowerment Section and Head of Institutional Section in Department of Cooperative and SMEs of Pasuruan; Cooperative Board and Manager in one of the cooperative in Pasuruan. Data collection was conducted with in-depth interview. The data used was primary data as qualitative data. Thematic analysis was used as analysis technique. The qualitative information was coded (translated) into qualitative data; followed by arrangement of pattern/theme; then encoding process (classifying pattern/theme into the relationships between categories); defining and describing the categories; and the last conclusion drawing. The result indicates that GCG has the uniqueness that enables its principles integrated of spirituality element.  The essence of the spirituality value is cooperative values and its embodiment as an effort to revitalyze the cooperative values. The finding of this research was Fishbone Diagram of Spirituality Values on GCG Principles